Crystallization of single-walled carbon nanotubes from a dilute solution. (22nd February 2021) - Uchida, Tetsuya; Tsugawa, Naoya; Yoshida, Satoru; Tohnai, Natsuki
Abstract: Single-walled carbon nanotubes (SWNTs) with lengths of several hundred nanometers were crystallized from dilute solutions, and slender lath-shaped SWNT crystals were obtained. The SWNTs were oriented along the long axis of the lath-shaped crystal, and the obtained crystals were two-dimensional crystals comprising hexagonally close-packed SWNTs. A relatively long SWNT acted as a crystalline nucleus. The length of the SWNT used for crystallization affected the morphology and growth rate of the crystals. Higher crystallization temperature shortened the time to precipitation, and the diffusion of SWNTs dominated the crystal growth of SWNT crystals. Because the short SWNTs were rigid with a wide length distribution, their tube ends were inevitably included in the crystals, resulting in crystal defects, such as lattice curvature and edge dislocations. These defects were directly observed by high-resolution electron microscopy. The mechanism for the crystallization of the SWNTs was proposed based on the observed morphologies, crystal defects, and crystallization process. Graphical abstract: Image 1 Highlights: Single-walled carbon nanotube (SWNT) crystals were prepared from dilute solutions. SWNTs were oriented along the long axis of the lath-shaped crystals. Crystals were two-dimensional and hexagonally close-packed. Crystal growth was dominated by diffusion. A possible mechanism for the crystallization was proposed.